Nutrition and Congruent Care Improve Wellbeing of Residents With Dementia in Slovenian Care Homes - KejŽar, Anamarija; Rihter, Liljana; Sajovic, Jakob; Drevenšek, Gorazd (Frontiers in Nutrition, 2022)
Introduction: Current nutritional strategies for people with dementia focus on nutritional regimens, although congruent care for people with dementia has been increasingly recognised to improve their wellbeing. This includes consistency of care, respecting the bio-psycho-social factors, emphasizing the importance of participation, and congruence with the individual’s capabilities. When applied to the nutritional aspects of care, it empowers people with dementia to have an active role in their care and during meals. Congruent care has shown promising results in improving the quality of life of residents, reducing negative social interactions and daily intake of medicines. Methods: A mixed qualitative-quantitative study was carried out. Seven homes that have implemented congruent care and five who have not implemented it agreed to participate (of 102 homes in Slovenia). Content analysis of focus group interviews and qualitative comparative analysis were carried out to establish how congruent care was implemented and to describe the differences in care between the two groups of homes. Frequencies and assigned importance of statements relating to nutritional care were statistically compared. A linear regression analysis of the data on medication as required that was available for the participating homes was carried out. Results: Congruent care improved the wellbeing of the people with dementia, as observed by caregivers. The homes that had implemented congruent care focused more on the food choice aspects of nutritional care (p = 0.0474), while the others were more attentive to the dietary intake aspects (p = 0.0067). In the homes that had congruent care, both caregivers and management reported that the number of prescriptions decreased, which is supported by the results of the linear regression (R2=78.4, p = 0.005), although the data available is limited. Conclusion: The people with dementia in the care homes that had congruent care were observed to have improved in mood, attitudes towards eating and wellbeing, as reported by caregivers. The homes that implemented congruent care reported a notable reduction in the use of medicine as required. A model of implementation of congruent nutritional care for people with dementia is presented.